Processos psicossociais de sofrimento e adoecimento em professores da rede pública de São Paulo durante a pandemia - Matos, Ronaldo dos Santos (2022)
This investigation has as its general objective to apprehend the meanings referring to the exercise of teaching during the isolation resulting from the pandemic caused by the “Covid-19 outbreak, as well as the meanings of the psychosocial processes of suffering and/or illness experienced throughout this journey, by an educator from the São Paulo educational public system. The study is based on the theoretical-methodological framework of Socio-Historical Psychology, which was constituted by the Historical and Dialectical Materialism, and which makes it possible to analyze the psychosocial processes through which the precariousness and, consequently, the incidences of favorable conditions to suffering and illness were potentiated as a result from professional practice without naturalizations and/or dichotomizations being produced. The analysis and interpretation procedure are a result of reports obtained through three reflective interviews. From there, the interviewed teacher presented her considerations about the experiences carried out in the aforementioned course – between March 2021 and the first semester of 2022. In this context, a proposal for the Nuclei of Meaning was made possible in accordance with the productions of Aguiar and Ozella (2006 and 2013); Aguiar, Soares and Machado (2015). The analyzes produced make it possible to infer the inequalities, precariousness, and due to the intensification of vulnerabilities to which students and their families were exposed, and concomitantly, denounce the consequences of teaching during such situations. It is hoped that this paper can contribute to the reflection on the psychosocial processes of suffering and illness arising from the performance of teaching work, in the face of the hardships to which the poorest part of the pollution was subjected